"Grain Gamelan": Adaptation of One More Grain Band's Songs to Gamelan Pelog Slendro - Gunawan, Iwan; ZZ, Afdhal Zikri; G, Sailendra Bedantara (Resital: Jurnal Seni Pertunjukan, 2023)
"Grain Gamelan": Adaptation of One More Grain Band's Songs to Gamelan Pelog Slendro. Based on a recording project initiated by the label "Yantra" through one of the musicians of the group "one more grain", Daniel Patrick Quinn, the author was asked to adapt songs from their group to gamelan instruments. The songs use Western instruments that use a very different tonal system from gamelan. The phenomenon of the difference in tone system between Western instruments and gamelan is still a dilemma, especially when music creators have the idea to combine the two types of instruments. The purpose of this writing is to reveal the artistic process of working on One More Grain Band songs adapted to gamelan with the pelog slendro tone system. The method used is practice-led research/practice-based research by doing exploration, simulation, and practice. Artistically, the songs of one more grain band have repetitive patterns with a tendency to use only one chord and each pattern played has changes that can be interpreted openly by the musician. Both of these have the same principles as traditional gamelan music. In the composing process, an approach was found using a mixed 10-tone system of pelog and slendro tunings of Javanese gamelan tumbuk nem. Through the use of DAW, the adaptation process can be well organized and measured to produce audio simulations and notations that are ready to be played by musicians directly. In the process of practicing with the musicians, various communication and interpretation problems were encountered in adapting this work. Based on the results achieved, the adaptation of "One More Grain" songs to gamelan has new nuances and perspectives that can enrich the repertoire of gamelan music globally.